1979
DOI: 10.1128/aac.15.2.258
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Resistance in Malaria: Accessibility of Drug Receptors to Mefloquine

Abstract: The process of mefloquine accumulation was studied in mouse erythrocytes infected with either Plasmodium berghei CS (chloroquine susceptible) or P. berghei CR (chloroquine resistant). In both cases, mefloquine was accumulated by a saturable process with an apparent dissociation constant of 2.5 x 106 M and an apparent maximal capacity of 700 ,umol per kg of erythrocyte pellet; uninfected mouse erythrocytes accumulated more than half as much mefloquine as infected erythrocytes. The process of accumulation was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, as has been pointed out in several studies, 5,75,77 this is not what is observed when comparing MQ vs. CQ accumulation experimentally; in fact, they are much more similar in magnitude, and certainly do not appear to differ by 3 orders of magnitude. 66,75,77 Figure 2 A:Predicted net fold accumulation of either CQ (circles) or MQ (squares) in DVof various pH (the X-axis) at fixed blood pH of 7.33. Note the huge differences predicted for CQ vs. MQ.…”
Section: B Partitioning Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, as has been pointed out in several studies, 5,75,77 this is not what is observed when comparing MQ vs. CQ accumulation experimentally; in fact, they are much more similar in magnitude, and certainly do not appear to differ by 3 orders of magnitude. 66,75,77 Figure 2 A:Predicted net fold accumulation of either CQ (circles) or MQ (squares) in DVof various pH (the X-axis) at fixed blood pH of 7.33. Note the huge differences predicted for CQ vs. MQ.…”
Section: B Partitioning Theorymentioning
confidence: 99%
“…27,63,64 As early as 1967, 65 the likelihood of important CQ-heme interactions was realized, and the idea gained further momentum via the work of Fitch and colleagues. 66 Chloroquine (CQ) is one of the most successful drugs of all time because: (1) it is inexpensive, (2) it is a stable compound that travels well, (3) it can be tolerated in high doses (the therapeutic index is excellent), (4) it targets the heme digestion pathway of the intraerythrocytic malarial parasite. Additional inexpensive strategies based on Hb digestion and heme polymerization will remain an important avenue for therapy in the future.…”
Section: F U N D a M E N T A L S O F Q U I N O L I N E P H A R M A mentioning
confidence: 99%
“…Peak areas are directly compared with those of extracted standards. Recovery of mefloquine from plasma, in the range of 200-600 nglml, was between 91 and 99%; recovery of the metabolite (21a), in the range of 600-1800 nglml, was between 62 method was less than +5%. Using this method, levels of mefloquine and its metabolite were followed in the plasma of subjects up to 3 months following an oral dose of 1 g of the drug.…”
Section: F Determination In Biological Fluidsmentioning
confidence: 93%
“…62 and references cited therein) using P. berghei CS(ch1oroquine susceptible)-and P. berghei CR(ch1oroquine resistant)-infected mouse erythrocytes. The pattern of mefloquine accumulation in these two systems differs markedly from that of chloroquine accumulation.…”
Section: R8mentioning
confidence: 99%
“…Mefloquine has been reported to accumulate in P. falciparum-infected human red cells with relatively constant red cells to plasma concentration ratio of about 1-2. 26 It also has a high affinity for binding to red cell membranes 28,29 and the concentrations in red cell membranes could be 60-fold of the bathing medium and buffer saline. 30 Mefloquine is certainly one of the best antimalarial drugs for treatment and prophylaxis of malaria.…”
Section: Discussionmentioning
confidence: 99%